2023
DOI: 10.3390/cancers15041153
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric Impact of Intrafraction Prostate Motion and Interfraction Anatomical Changes in Dose-Escalated Linac-Based SBRT

Abstract: The dosimetric impact of intrafraction prostate motion and interfraction anatomical changes and the effect of beam gating and motion correction were investigated in dose-escalated linac-based SBRT. Fifty-six gated fractions were delivered using a novel electromagnetic tracking device with a 2 mm threshold. Real-time prostate motion data were incorporated into the patient’s original plan with an isocenter shift method. Delivered dose distributions were obtained by recalculating these motion-encoded plans on def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Faccenda et al [13] compared the dosimetric impact of intrafraction prostate motion in linac-based gated and non-gated SBRT treatments using the same device, dose prescriptions and constraints described above [11] , [12] . As expected, the authors found larger dose deviations in non-gated treatments due to intrafraction prostate motion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Faccenda et al [13] compared the dosimetric impact of intrafraction prostate motion in linac-based gated and non-gated SBRT treatments using the same device, dose prescriptions and constraints described above [11] , [12] . As expected, the authors found larger dose deviations in non-gated treatments due to intrafraction prostate motion.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, prostate volumetric modulated arc therapy (VMAT)-SBRT treatments are commonly planned with multiple flattening filter free (FFF) arcs, generally two [8] , [9] , [10] , [11] , [12] , [13] , [14] but even up to four [15] , thus requiring intrafraction motion monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…The benefit of reducing treatment time in prostate SBRT to potentially mitigate the effects of intrafraction motion has been demonstrated by several groups [ 14 , 15 , 16 , 17 , 18 , 19 ]. In previous studies [ 19 , 26 ], it has been demonstrated that the probabilities of prostate motion >3 mm and >5 mm within 5 min were 1.8% and 0.0%, respectively, and that intrafraction prostate motion had a noticeable impact on some individual fractions using 2 mm PTV margins but tended to average out when considering the cumulative effect over 4–5 treatment fractions. The use of SA VMAT plans as planning strategy to shorten the delivery time has been widely recommended as well [ 34 , 37 , 38 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, due to the higher doses per fraction and fewer fractions compared to conventional treatment, SBRT requires more precise dose gradients with tighter margins. Since several studies [ 14 , 15 , 16 , 17 , 18 , 19 ] have identified substantial and unpredictable motion of the prostate during the beams’ delivery, significant intrafractional displacement can have a relevant impact on treatment, potentially leading to either excessive exposure of healthy tissue or insufficient target coverage [ 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The intrafraction motion of the prostate can significantly impact delivery to the prostate gland. The prostate gland is a mobile organ, and larger movements during treatment could result in irradiation of healthy tissue or underdosing of the tumor target volume, adversely affecting tumor control [ 4 , 5 ]. Conversely, patients with higher intrafraction motion might benefit from continuous tracking and intrabeam adjustments through smaller required safety margins [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%